Using online spaces to recruit Kenyan queer womxn and trans men in restrictive offline settings - Stephanie Haase; Virginia Zweigenthal; Alex Müller (BMC, 2022)
Abstract Background Understanding and addressing healthcare and service delivery inequalities is essential to increase equity and overcome health disparities and service access discrimination. While tremendous progress has been made towards the inclusion of sexual and gender minorities in health and other research, gaps still exist. Innovative methods are needed to close these. This case study describes and reflects on using online-based data collection to ascertain sexual health decision-making and health service utilisation among Kenyan queer womxn and trans men. Methods Case study The study used a mixed-methods approach in two phases with triangulated quantitative and qualitative elements. Both elements used web-based technology to gather data. Results Using online spaces to recruit and collect data from queer womxn and trans men exceeded expectations. A total of 360 queer womxn and trans men responded to the digitally distributed survey, and 33 people, queer womxn and trans men, as well as key informants, participated in the interviews, which were primarily conducted on Zoom and Skype. The case study analyses the risks and benefits of this approach and concludes that online sampling approaches can mitigate risks and enable effective and safe sampling of a marginalised group in a restrictive legal setting: Kenyan queer womxn and trans men. Conclusion Using online spaces when researching marginalised populations could effectively overcome risks around stigma, discrimination and violence. It could be an effective way to understand these populations' healthcare needs better. Factors contributing to success included building trusting relationships with key members of the community, strategic and opportune timing, a nuanced understanding of the mobile landscape, and carefully chosen safety and security measures. However, it should be noted that conducting research online could increase the risk of further marginalising and excluding those without access to web-based technology.